Whole Health coaching to rural Veterans through telehealth: Advantages, gaps, and opportunities - LeBeau, Kelsea; Varma, Deepthi S.; Kreider, Consuelo M.; Castañeda, Gail; Knecht, Cheri; Cowper Ripley, Diane; Jia, Huanguang; Hale-Gallardo, J. (Frontiers in Public Health, 2023)
Background The Veterans Health Administration (VHA) is one of the largest providers of telehealth in the United States and continues to lead the way in transforming healthcare services. VHA has been implementing its Whole Health (WH) initiative since 2018, a proactive practice empowering patients to take charge of their health and well-being. A key facilitator of the WH initiative is the WH coach who partners with Veterans to achieve their health-related goals. A gap exists in the literature regarding the understanding of WH coaches’ use of telehealth to engage rural-residing Veterans. COVID-19 unexpectedly interrupted in-person VHA delivery of care, including WH coaching which primarily relied on in-person delivery and focused less on telehealth. During the pandemic, WH coaches had to adapt and integrate different modalities to engage their Veteran patients. We examined WH coaches’ approaches to extending coaching to rural Veterans via technology, emphasizing the advantages of telehealth, existing gaps in telehealth delivery, and opportunities for telehealth as a coaching modality. Methods This project was implemented as part of a larger mixed methods evaluation regarding WH coaching for rural Veterans; this manuscript presents the findings from the qualitative data from the larger study. The qualitative dataset is comprised of data collected using three different qualitative methods: four focus groups (n = 11; 3–4 participants per group), in-depth individual interviews (n = 9), and open-ended responses from a national web-based survey (n = 140). Focus group, in-depth interview, and open-ended survey data were collected sequentially and separately analyzed following each wave of data collection. Findings from the three analyses were then collaboratively merged, compared, reorganized, and refined by the evaluation team to create final themes. Results Three final themes that emerged from the merged data were: (1) Advantages of Telehealth; (2) Telehealth Gaps for Rural Veterans, and (3) Strategies for Bridging Telehealth Gaps. Themes explicate telehealth advantages, gaps, and opportunities for rural Veteran WH coaching. Conclusion Findings highlight that video telehealth alone is not sufficient for meeting the needs of rural Veterans. Digital technologies hold promise for equalizing health access gaps; however, both human factors and broadband infrastructure constraints continue to require WH coaches to use a mix of modalities in working with rural Veterans. To overcome challenges and bridge gaps, WH coaches should be ready to adopt a blended approach that integrates virtual, in-person, and lower-tech options.